Analysis of Students' Enviromental Literacy Skill in Adiwiyata High Schools in Semarang - Zakiyatul Maghfiroh; Nugroho Edi Kartijono (Universitas Negeri Semarang, 2024)
The PBLHS initiative in schools aims to cultivate individuals with strong environmental literacy skills, which can contribute to reducing environmental issues. The results of the interview suggest that the schools in Adiwiyata have not carried out an assessment of the environmental literacy of their students, despite its critical role in enhancing policies for PBLHS implementation. This study aims to assess the environmental literacy of high school students in Semarang regarding their knowledge, cognitive skills, and attitudes. The research used a descriptive quantitative method, surveying 375 respondents from class XI MIPA in the second semester of 2022/2023 from high schools that were awarded Adiwiyata. The research instrument utilized the environmental literacy assessment framework developed by NAAEE and adapted to high school biology materials. The environmental literacy of Class XI MIPA students at Adiwiyata High School in Semarang City is categorized as moderate in terms of knowledge, cognitive skills, and attitudes, with an average score of 35 for knowledge, 37 for cognitive skills, and 45 for attitudes. Knowledge of ecological systems, the impact of gas pollutants on environmental pollution, and the ability to identify environmental issues are critical areas for improvement. Additionally, students must be responsible for protecting the environment and have a strong sense of self-efficacy. Factors that influence students' environmental literacy skills include individual, school, and family environment, particularly in developing habits that promote environmental protection.